Innovative diagnostic tools for early detection of Alzheimer's disease. Issue 5 (15th November 2014) - Laske, Christoph; Sohrabi, Hamid R.; Frost, Shaun M.; López-de-Ipiña, Karmele; Garrard, Peter; Buscema, Massimo; Dauwels, Justin; Soekadar, Surjo R.; Mueller, Stephan; Linnemann, Christoph; Bridenbaugh, Stephanie A.; Kanagasingam, Yogesan; et al.
Abstract: Current state‐of‐the‐art diagnostic measures of Alzheimer's disease (AD) are invasive (cerebrospinal fluid analysis), expensive (neuroimaging) and time‐consuming (neuropsychological assessment) and thus have limited accessibility as frontline screening and diagnostic tools for AD. Thus, there is an increasing need for additional noninvasive and/or cost‐effective tools, allowing identification of subjects in the preclinical or early clinical stages of AD who could be suitable for further cognitive evaluation and dementia diagnostics. Implementation of such tests may facilitate early and potentially more effective therapeutic and preventative strategies for AD. Before applying them in clinical practice, these tools should be examined in ongoing large clinical trials. This review will summarize and highlight the most promising screening tools including neuropsychometric, clinical, blood, and neurophysiological tests.